2009
DOI: 10.1063/1.3118500
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of individual magnetic particle motion near a chip surface

Abstract: We describe an analysis of the dynamics of individual superparamagnetic micro-and nanoparticles in order to quantify their magnetic properties and mobility near a chip surface. The particles are attracted to the chip surface by integrated microscopic current wires. We show that it is possible to accurately analyze particles with a diameter of about 1 m by the magnetophoretic movement between current wires because of the very high field gradients. This reveals distinct differences in volume susceptibilities of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…F m , calculated for an SPB with a radius of 1.4 lm and a susceptibility of 1.2 46 in a solution with a viscosity of 1 Â 10 À3 PaÁs, has a maximum value of 2.2 pN at the edges of the disk, which is sufficient to trap SPBs. 8,9,13,15,[20][21][22][26][27][28][29][30][31][32][33][34][35]47 Fig . 2(c) shows the velocity of an SPB during the trapping process.…”
Section: -4mentioning
confidence: 99%
“…F m , calculated for an SPB with a radius of 1.4 lm and a susceptibility of 1.2 46 in a solution with a viscosity of 1 Â 10 À3 PaÁs, has a maximum value of 2.2 pN at the edges of the disk, which is sufficient to trap SPBs. 8,9,13,15,[20][21][22][26][27][28][29][30][31][32][33][34][35]47 Fig . 2(c) shows the velocity of an SPB during the trapping process.…”
Section: -4mentioning
confidence: 99%
“…In current study, the immobilizing frequency was found to be 5.5 and 12.0 Hz for the 1.0 and 2.8 m diameter beads, respectively. Due to the magnetization differences in given lot of beads 15 , the beads shown different velocity of transport at low rotation frequencies. The threshold frequency introduced a minimum frequency for immobilizing majority of corresponding beads on micro-magnets array.…”
Section: Resultsmentioning
confidence: 99%
“…However, the Brownian motion of the magnetic beads becomes more and more obvious with the increase of temperatures. To verify the influence of Brownian motion the following relation is applied (Ommering et al 2009):…”
Section: Effect Of Fluid Temperaturementioning
confidence: 99%